Risquer le pédagogique, entre héritage et modernité - Loïc Chalmel (Nantes Université, 2011)
Distrusting models claim to universal and claiming an unwavering commitment to a singular experience, educator's subjective "place", however, appears to be a rich area of intellectual creation in tension between theories and practices. Conservatory memory value choices made by particular individuals in particular socio-historical context, it collates all the alternatives that can be examined further, suggesting benchmarks for action, if only the "following" does not lose memory...The historian of pedagogical ideas involved in this duty of memory, remodelling materials of the past without reproducing the same. The transition from education to history is not just a matter of epistemology: writing the history of educational ideas, it's both be able to project themselves into the world of other, supportive of his loneliness, and to understand what motivates choice, forced his freedom of action, deconstructing a functioning unit to clarify the linkages between different types of knowledge that constitutes it.